Konsep Diri Tokoh Iyan dalam Novel Iyan Bukan Anak Tengah karya Armaraher - Ilona Pasya Defghi; Hedya Novtansa Nugraheni; Eva Dwi Kurniawan (PT. Gudang Pustaka Cendekia, 2023)
The study was intended to identify the concept of the main character in the novel Iyan Not a Middle Child by Armaraher. The method used in this study is a descriptive qualitative description to describe phenomena that people experience, the description carried out in word and language in a context that leads to the theory proposed by Carl Rogers regarding the concept of self and using a literary psychology approach to unravel the psychological elements of the fictional character contained in the literature. Research shows that the main character in the novel Iyan Not a Middle Child by Armaraher had a negative self-concept, which involved an imbalance between the ideal self and real self in the character Riyan. It deeply influences how the figure sees himself and breathes his life, as well as how he interforms with others from absence unconditional positive regard.